2006
DOI: 10.1111/j.1743-6109.2005.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behaviors and Mental Perception, Satisfaction and Expectations of Sex Life in Men and Women in France

Abstract: Aim To analyze behaviors, mental perception, satisfaction, and expectations relating to sexuality in France. Methods A total of 1,002 subjects (483 men and 519 women) aged 35 years and over in a representative sample of the French population were surveyed by phone using a dedicated questionnaire in November 2003. Main Outcome Measures Sexual behaviors and men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
54
3
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 23 publications
(31 reference statements)
11
54
3
6
Order By: Relevance
“…5,16 Colson et al studied a sample of 1,002 participants and concluded that, during sexual intercourse, multiple orgasms and intimacy are the most important aspects for the majority of participants, followed by foreplay and vaginal penetration. 23 Poor foreplay quality correlates better with orgasmic dysfunction and arousal than with sexual satisfaction. This means that some women desire better foreplay activity, targeting a better arousal or reaching an orgasm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,16 Colson et al studied a sample of 1,002 participants and concluded that, during sexual intercourse, multiple orgasms and intimacy are the most important aspects for the majority of participants, followed by foreplay and vaginal penetration. 23 Poor foreplay quality correlates better with orgasmic dysfunction and arousal than with sexual satisfaction. This means that some women desire better foreplay activity, targeting a better arousal or reaching an orgasm.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, arousal can precede desire in the female sexual cycle and be the sexual trigger for some women, proving its importance for the quality of sexual life. [17][18][19][20][21][22][23][24][25][26] Lubrication problems are the second most common sexual complaint in women, reported being present in up to 39% of cases. 5,26 In Brazil, 27 to 37% women have arousal problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study outcomes were sexual behavior, mental perceptions of sexuality, level of satisfaction, expectations concerning sex life, and sexual complaints and dysfunctions. Other data have been more thoroughly addressed in other publications (Colson et al, 2006) [11], (Colson et al, 2007) [12] (Lemaire et al, 2009) [13] or will be treated in future work.…”
Section: Survey and Study Outcomesmentioning
confidence: 99%
“…Tendenziell zeichnet sich in diesen Studien eine Diskrepanz zwischen den sexuellen Bedürfnissen der Män-ner und denen der Frauen ab. So berichten Männer beispielsweise im Vergleich zu Frauen über eine größere Anzahl an Sexualpartnern [24] und über häufige-ren Geschlechtsverkehr (GV; [6]). Auch scheinen Männer mit ihrem Sexualleben im Vergleich zu Frauen seltener zufrieden zu sein [23].…”
unclassified